2013
DOI: 10.1016/j.nicl.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic therapy in Parkinson's disease decreases cortical beta band coherence in the resting state and increases cortical beta band power during executive control

Abstract: It is not yet well understood how dopaminergic therapy improves cognitive and motor function in Parkinson's disease (PD). One possibility is that it reduces the pathological synchronization within and between the cortex and basal ganglia, thus improving neural communication. We tested this hypothesis by recording scalp electroencephalography (EEG) in PD patients when On and Off medication, during a brief resting state epoch (no task), and during performance of a stop signal task that is thought to engage two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
124
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 59 publications
11
124
0
Order By: Relevance
“…This is consistent with previous work, using either EEG, MEG, or ECoG, which has not shown a consistent alteration of cortical beta power in PD 6, 18, 27-29 . Similarly, there were no differences in broadband gamma power (50-150 Hz, excluding 60 and 120 Hz) (p > 0.16, Figure 3C-D ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous work, using either EEG, MEG, or ECoG, which has not shown a consistent alteration of cortical beta power in PD 6, 18, 27-29 . Similarly, there were no differences in broadband gamma power (50-150 Hz, excluding 60 and 120 Hz) (p > 0.16, Figure 3C-D ).…”
Section: Resultssupporting
confidence: 93%
“…In that study, coherence was measured between all EEG contact pairs in PD patients and was found to be reduced with medications and DBS. That reduction with medications was replicated with the same dataset reported here, in a previous publication 18 .…”
Section: Discussionsupporting
confidence: 83%
“…Although the exclusion criteria in our study have included atypical parkinsonism, neuropsychiatric condition and any other severe illness, it is still required longitudinal study to identify whether the observed changes in PE or OI are specific to PD rather than age-related parkinsonism or multiple system atrophy. Moreover, it has been shown that the dopaminergic replacement therapy has long effects on sensory-motor circuitry (George et al 2013;Herz et al 2014). All the patients in our study have received levodopa drugs.…”
Section: Discussionmentioning
confidence: 98%
“…This makes a direct connection to patients with Parkinson’s Disease (PD) who are typically ‘stuck in set’, especially with regard to switching behavior (in addition to their classic motor symptoms) (Bowen et al, 1975; Lees and Smith, 1983; Taylor et al, 1986). PD is characterized by over-synchrony between basal ganglia and cortex (Brown, 2003; George et al, 2013; Swann et al, 2015); and it is thought that this ‘locking’ prevents cortico-basal-ganglia circuits from operating properly. Indeed, multiple studies show PD patients off treatment are impaired at stopping (George et al, 2013; Obeso et al, 2014; Obeso et al, 2011; Swann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PD is characterized by over-synchrony between basal ganglia and cortex (Brown, 2003; George et al, 2013; Swann et al, 2015); and it is thought that this ‘locking’ prevents cortico-basal-ganglia circuits from operating properly. Indeed, multiple studies show PD patients off treatment are impaired at stopping (George et al, 2013; Obeso et al, 2014; Obeso et al, 2011; Swann et al, 2011). We hypothesize that the mental inflexibility in PD is at least partly explained by a system that is not properly interruptible by new information (because the STN-mediated interrupt is ineffective due to oversynchrony).…”
Section: Discussionmentioning
confidence: 99%